Corporate Governance, Ownership Structure and Expropriation of Rights: Case of Malaysian Small and Medium Enterprises - Umrani, Aamir Iqbal; Johl, Satirenjit Kaur (International Journal of Economics and Financial Issues, 2016)
SMEs serve as the financial backbone of the developed and developing economies, and a major contributor in many countries’ GDP. A sustainable SME sector is vital for a developing country like Malaysia where SMEs represent 99.2 % of the overall business establishment and a major employment sector in the country. Although, the Malaysian SME sector faces a critical problem, which results in 50 % of SMEs collapse during the first five years of operation and a 60% rate of failure among SMEs. in addition, unauthorized use of company property, misappropriating company funds, making false statements, illegal investment schemes and many other allegations have been put on the Malaysian SME owners and directors in the past. The objective of this paper is to investigate the Malaysian SMEs structure, past allegations and the corporate governance practices in the medium sized manufacturing SMEs. This study has adopted a qualitative approach, face-to-face interviews were conducted with SME owners/directors, and regulatory body officials. The results show that the Malaysian SMEs are mainly family based and higher management positions are kept by the family. Furthermore, it was revealed that there is no corporate governance code for the SMEs.This provides room for the family to expropriate minority shareholders’ rights and perform illegal activities. Hence, the results stressed on the need of the implementation of corporate governance code for Malaysian SMEs. Keywords: Corporate Governance, Ownership Structure, Family Ownership, Foreign Ownership, Expropriation of rights JEL Classifications: L25, L26, L60, M10, Y2